OC-026 The Clinical and Phenotypic Assessment of Seronegative Villous Atrophy; A Prospective UK Centre Experience Evaluating 200 Cases over a 15 Year Period (2000–2015). (17th August 2016) - Aziz, I; Peerally, MF; Barnes, JH; Kandasamy, V; Vergani, P; Cross, SS; Sanders, DS
Abstract : Introduction: Complex cases of seronegative villous atrophy (SNVA) have been attributed to celiac disease or angiotensin-2-receptor-blockers. However, this may not reflect SNVA in general. We aimed to provide diagnostic outcomes in all newcomers with SNVA and identify predictive factors. Methods: Over a 15 year period (2000–2015) we prospectively evaluated 200 adult patients with SNVA at a UK secondary/tertiary-care centre. A diagnosis of either seronegative celiac disease (SNCD) or SN-non-CD was reached. Baseline comparisons were made between the groups, with 343 seropositive CD subjects serving as controls Results: Of the 200 SNVA cases, SNCD represented 31% (n = 62) and SN-non-CD 69% (n = 138). The HLA-DQ2/8 genotype was present in 61%, with a 51% positive predictive value for SNCD. The breakdown of identifiable causes in the SN-non-CD group include infections (27%, n = 54), inflammatory/immune-mediated disorders (17.5%, n = 35) and drugs (6.5%, n = 13; two cases related to angiotensin-2-receptor-blockers). However, no cause was found in 18% (n = 36) and of these 72% (n = 26/36) spontaneously normalised duodenal histology whilst consuming a gluten-enriched diet. Following multivariable logistic regression analysis a novel independent factor associated with SN-non-CD was non-Caucasian ethnicity (odds ratio 17.2, p = 0.002); in fact, 66% of non-Caucasians had Helicobacter pylori and/or alternate gastrointestinal infections. On immunohistochemistry all villous atrophy groups stained positive for CD8-T-cytotoxic intraepithelial lymphocytes. However, additional CD4-T-helper intraepithelial lymphocytes were occasionally seen in SN-non-CD mimicking the changes associated with refractory CD. Conclusion: Most patients with SNVA do not have celiac disease or angiotensin-2-receptor-blocker enteropathy. Further, a subgroup shows spontaneous histological resolution whilst consuming gluten. The presence of non-Caucasian ethnicity should prompt search for an infective aetiology. The role of phenotyping intraepithelial lymphocytes for diagnostic purposes can potentially be misleading. Disclosure of Interest: None Declared